Transcription Factor Bcl11b Controls Effector and Memory CD8 T cell Fate Decision and Function during Poxvirus Infection - Abboud, Georges; Stanfield, Jessica; Tahiliani, Vikas; Desai, Pritesh; Hutchinson, Tarun E.; Lorentsen, Kyle J.; Cho, Jonathan J.; Avram, Dorina; Salek-Ardakani, Shahram (Frontiers in Immunology, 2016)
CD8+ T cells play an important role in host resistance to many viral infections, but the underlying transcriptional mechanisms governing their differentiation and functionality remain poorly defined. By using a highly virulent systemic and respiratory poxvirus infection in mice, we show that the transcription factor Bcl11b provides a dual trigger that sustains the clonal expansion of virus-specific effector CD8+ T cells, while simultaneously suppressing the expression of surface markers associated with short-lived effector cell (SLEC) differentiation. Additionally, we demonstrate that Bcl11b supports the acquisition of memory precursor effector cell (MPEC) phenotype, and thus its absence causes near complete loss of lymphoid and lung-resident memory cells. Interestingly, despite having normal levels of T-bet and Eomesodermin, Bcl11b-deficient CD8+ T cells failed to execute effector differentiation needed for anti-viral cytokine production and degranulation, suggesting a non-redundant role of Bcl11b in regulation of this program. Thus, Bcl11b is a critical player in fate decision of SLECs and MPECs, as well as effector function and memory formation.